MODEL TECHNO-STEWARD LEADERSHIP: IMPLEMENTASI PRINSIP IMAGO DEI DALAM KEPEMIMPINAN KRISTEN UNTUK MENJAWAB TANTANGAN KECERDASAN BUATAN (AI) - Sandiki, Reza; Widianto, Alwi (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2026)
The disruption of Artificial Intelligence (AI) brings not only technological transformation but also profound anthropological and ethical challenges to our understanding of humanity and the practice of leadership. This study aims to construct a responsive Christian leadership framework by arguing that the doctrine of Imago Dei (humanity as the image of God) provides a crucial theological-ethical foundation for navigating the AI era. Using an interdisciplinary literature study and exploratory-normative conceptual analysis, this research first identifies three main challenges: (1) anthropological reductionism that reduces humans to mere data, (2) dislocation of responsibility (responsibility gap) due to black box systems, and (3) threats to the human vocation for work and creativity. In response, the study derives four operational principles from Imago Dei: the Principles of Dignity, Stewardship, Relationality, and Justice & the Common Good. These principles are then operationalized into three domains of leadership practice: (a) in strategic decision-making through the implementation of an Ethical Impact Assessment enriched with theological-anthropological considerations; (b) in building organizational culture through creating interdisciplinary dialogue spaces (technicians, ethicists, theologians) and narrative-based ethics training rooted in Biblical stories; and (c) in public engagement through advocacy for human-centric and just AI policies. As a synthesis, this research proposes the "Techno-Steward Leadership" model as an ideal paradigm, requiring deep anthropological vision, critical technological literacy, ethical courage (moral courage), and commitment to character formation. In conclusion, this study affirms that Christian leadership in the AI era is called to function as wise technological stewards, directing digital innovation to honor human dignity as Imago Dei and build the common good in society.